KRITIK SOSIAL DALAM KARIKATUR (Analisis Semiotika Terkait Kritik Sosial dalam Postingan Instagram Gejayan Memanggil) - Agusly Irawan Aritonang (Institute of Research and Community Outreach - Petra Christian University, 2022)
Social criticism arises when there is no satisfaction with an existing order. In the political context, social criticism is often conveyed when the government system doesn’t run optimally and ideally. Many parties can convey social criticism and many ways how to to convey social criticism. The emergence of social media makes it easier to convey social criticism. Caricatures have long been known as a form of conveying social criticism, both in the form of satire and sarcastic statements. This paper seeks to see how social criticism is conveyed through the form of caricatures. Using Pierce's semiotics method, tracking the combination of icons, indexes, and symbols that appear from the caricatures posted by the @gejayanmemanggil account. The chosen caricature is a caricature that is the result of the creation by @gejayanmemanggil account admin, not a reposted caricature because it is the result of someone else's creation. As a result, criticism emerged targeting President Joko Widodo and his circle including his ministers as being the contradictive, anti-criticism and stifling freedom of expression. Criticism to members of the Council was also conveyed for not immediately ratifying the law that was deemed important as well as criticism of the Omnibus Law. In addition, a post related to Marsinah was raised as a reminder and a moral gesture to urge solve of her case.